Proceedings: Students in Polar and Alpine Research Conference 2023 - Holuša, Jakub; Kadlec, Martin; Stringer, Christopher (Masaryk University Press, 2023)
Proceeding of conference abstracts from "Students in Polar and Alpine Research Conference" organized 14 to 15 September 2023 at Department of Geography, Masaryk University, in Brno. The proceedings contain 12 abstracts of scientific topic of young researchers done in polar and alpine regions.